Principles and practice of sport management - Masteralexis, Lisa Pike; Barr, Carol A.; Hums, Mary A. (Jones & Bartlett Learning, 2014)
From the basic knowledge and skill sets of a sport manager to the current trends and issues in the sport management industry, the Fifth Edition of this best-selling text provides the foundation for students as they study and prepare for a variety of sport management careers. The authors, all well-known sport industry professionals, show students how to apply their new knowledge and skills to any segment in the sport industry from high school to the international arena. Principles and Practice of Sport Management, Fifth Edition continues to offer historical perspectives as well as thoughts about current and future industry issues and trends. It has, however, undergone substantial content updates in every chapter, including the inclusion of new developments or managerial approaches happening in the sport world, as well as the addition of new chapters on new media in sport and club management.